The specificities of self assessment in adolescents with scoliosis - Kolomiets, Solomia (Psychiatry, Neurology and Medical Psychology, 2018)
Scoliosis is one of the most common diseases of the musculoskeletal system, which affects people of childhood and adolescence and, changing the shape of the spine, distorting posture, affects the self-assessment, in particularthe image of the body. Along with solving complex orthopedic issues, the psychosocial aspect remains mportant, in particular, the study of the features ofthe formation of the internal picture of the disease, its prerequisites and the impact on the process of helping patients with scoliosis. The article presentsthe results of the study of the specificities of selfassessment of adolescents with scoliosis. By the inclusion-exclusion criteria, 169 adolescents (boys and girls) were included in the study with grade III and III-IV scoliosis. The tendencies towards a decrease in the level of self-esteem for groups of adolescents with different severity of orthopedic disorders in scoliosis, and the relationship between the level of self-assessment and the degree of defeat are determined. Gender difference in the self-correlation of adolescents with scoliosis is also described.